Antimicrobial activity of cyathane derivatives from Cyathus subglobisporus BCC44381. Issue 48 (29th November 2018) - Nitthithanasilp, Sutichai; Intaraudom, Chakapong; Boonyuen, Nattawut; Suvannakad, Rapheephat; Pittayakhajonwut, Pattama
Abstract: Six unknown cyathane diterpenes, named cyathinins A – E, and 10-hydroxyerinacine S, were isolated from Cyathus subglobisporus BCC44381 along with six known compounds, striatoid C, striatin C, striatals A, C, D, and glochidone. The chemical structures were determined by means of high resolution mass spectrometry (HRESI-MS) and nuclear magnetic resonance (NMR) spectroscopy. The absolute configurations were confirmed by X-ray diffraction analysis. The isolated active compounds exhibited antimalarial against Plasmodium falciparum (IC50 0.88–7.51 μM), antibacterial activities against Mycobacterium tuberculosis (MIC 25–50 μg/mL), Gram-positive bacteria of Bacillus cereus and Enterococcus faecium (MIC 0.78–50 μg/mL) and Gram-negative bacteria of Escherichia coli, Acinetobacter baumannii and Klebsiella pneumoniae in a presence of phenylalanine-arginine β-naphthylamide (MIC 3.13–50 μg/mL), antifungal activity against Candida albicans (IC50 8.6–80.3 μM) activities, and cytotoxic activity against both cancerous (MCF-7, KB, NCI-H187, IC50 0.36–28.32 μM) and non-cancerous (Vero, IC50 0.13–91.50 μM) cells. Graphical abstract: